(untitled) (Research, Society and Development, 2022)
Diabetes mellitus is one of the major concerns of the century due to the increase in its prevalence, and sequelae caused to individuals, such as blindness and lower limb amputation, as well as its mortality. There are two types of diabetes mellitus, Type I and Type II, the first being also called juvenile diabetes that occurs due to the partial or total inability of the individual to produce insulin, while the second type which is also called adult diabetes is caused by ineffective use of insulin produced by the body or the development of resistance to it. Dental treatment is extremely important for patients with diabetes mellitus, since this disease presents a series of manifestations and oral complications. This work aims to bring information about the dental treatment of patients with diabetes mellitus, which can serve as an informational base on this topic for dental students as well as professionals in the area. A descriptive narrative literature review was carried out, using as a bibliographic basis scientific articles published between the years 1997 and 2021, available in online databases such as PUBMed, BVSalud, Scielo and Google Scholar, all articles are available in Portuguese, were articles published outside this time frame and/or available in a foreign language are excluded. It is extremely important to design and implement diabetes awareness and control programs due to the socioeconomic consequences and damage caused to quality of life. It was obvious the importance of the dental surgeon in the multidisciplinary treatment of patients with diabetes mellitus, since the oral cavity can be affected so severely.